The role of philosophy in the development and practice of nursing: Past, present and future. (19th July 2021) - Bender, Miriam; Grace, Pamela J.; Green, Catherine; Hopkins‐Walsh, Jane; Kirkevold, Marit; Petrovskaya, Olga; Paljevic, Esma D.; Sellman, Derek
Abstract: This article summarizes a virtual live‐streamed panel event that occurred in August 2020 and was cosponsored by the International Philosophy of Nursing Society (IPONS) and the University of California, Irvine's Center for Nursing Philosophy. The event consisted of a series of three self‐contained panel discussions focusing on the past, present and future of IPONS and was moderated by the current Chair of IPONS, Catherine Green. The first panel discussion explored the history of IPONS and the journal Nursing Philosophy . The second panel involved a reflection on the challenges of doing nursing philosophy in a research‐intensive context of a Canadian university and the history and current movements in nursing philosophy in the Nordic countries. The final panel involved presentations on the future potential for philosophy in/and for nursing, the critical connections between nursing philosophy and nursing theory, dismantling racism in nursing and the potential for process philosophy to help explore nursing's unique efficacy in creating possibilities for health. The panels were followed by a lively Q&A session with participants, of which there were 252 registrants from across the globe. The event underscored the wide and diverse interests of nurses in philosophical discussion and the need for more virtual events and other connective modalities bringing nurses together to discuss and analyze the value and potential of philosophy to better understand and advance nursing theory and practice.